Phytochemical and antioxidant analysis of medicinal and food plants towards bioactive food and pharmaceutical resources - Manyou Yu (Nature Portfolio, 2021)
Abstract Plants with medicinal properties play an increasingly important role in food and pharmaceutical industries for their functions on disease prevention and treatment. This study characterizes the phenolic composition and antioxidant activity of seven medicinal and food plants, including the leaves of Salvia officinalis L., Rosmarinus officinalis L., Olea europaea L., and Punica granatum L., as well as the leaves and young stems of Ruta graveolens L., Mentha piperita L., and Petroselinum crispum, Mill., by using colorimetric, chromatographic, and spectrophotometric assays. Results revealed that the hydro-methanolic leaf extracts of P. granatum (pomegranate) displayed the highest content of total phenols (199.26 mg gallic acid per gram of plant dry weight), ortho-diphenols (391.76 mg gallic acid per gram of plant dry weight), and tannins (99.20 mg epicatechin per gram of plant dry weight), besides a higher content of flavonoids (24 mg catechin per gram of plant dry weight). The highest antioxidant capacity measured by ABTS, DPPH, and FRAP (2.14, 2.27, and 2.33 mM Trolox per gram of plant dry weight, respectively) methods was also obtained in pomegranate leaf extracts, being 4–200 times higher than the other species. Such potent antioxidant activity of pomegranate leaves can be ascribed to the presence of different types of phenolic compounds and the high content in tannins, whilst phenolic acids and flavonoids were found to be the dominant phenolic classes of the other six plants. Consequently, despite the well-known antioxidant properties of these plant species, our study suggests pomegranate leaf can stand out as a relatively more valuable plant source of natural bioactive molecules for developing novel functional food-pharma ingredients, with potential for not only promoting human health but also improving bio-valorization and environment.